Multi‐Strategy Architecture of High‐Efficiency Electrocatalysts for Underwater Zn–H2O2 Batteries with Superior Power Density of 442 mW cm−2. Issue 12 (27th January 2022) - Yue, Cuiyu; Zhang, Nian; Zhu, Zhenjiang; Chen, Peng; Meng, Fancheng; Liu, Xiaosong; Wei, Xiangfeng; Liu, Jiehua
Abstract: A facile multistage regulated strategy is reported to synthesize ZnCo‐NC based carbon nanotubes including DMEA induced crystallization, Zn ion activation, and magnetic control growth of carbon nanotubes. Uniform Co distribution and the modulation of Zn, and their catalytic properties are carefully investigated by X‐ray absorption spectroscopy and X‐ray photoelectron spectroscopy. The surface contents of pyridinic N for the oxygen‐reduction reaction (ORR) and the surface contents of CoN x and high valence Co for the oxygen‐evolution reaction (OER) can be significantly modulated by Zn content in precursors and the sintering temperature. Furthermore, the catalyst also contains high specific surface areas, high porosity, and high electrochemical active surfaces. Therefore, the ZnCo‐NC based catalyst exhibits outstanding bifunctional electrocatalytic activities for ORR with a high E onset (1.02 V) and E 1/2 (0.91 V) and OER with low E j=10 (1.56 V), better than Pt/C and RuO2 . Importantly, the ZnCo‐NC based Zn–H2 O2 batteries achieve the superior power density of 442 mW cm −2, much higher than 238 and 198 mW cm −2 of Zn–air batteries with ZnCo‐NC based catalyst and Pt/C respectively. More importantly, the high‐power Zn–H2 O2 batteries can work well in underwater conditions while Zn–air batteries are out of work. Abstract : A facile multistage regulated strategy is herein proposed to synthesize ZnCo based N‐doped carbon nanotubes including N, N‐dimethylethanolamine induced crystallization of Zn/Co zeolitic imidazolate frameworks, Zn ion activation by reducing and volatilizing, and magnetic control growth of carbon nanotubes. The Zn–H2 O2 batteries with the electrocatalyst can achieve a high power density of 442 mW cm −2, 186% and 223% times as high as 238 and 198 mW cm −2 of Zn–air batteries with the catalyst and Pt/C respectively.